2016
DOI: 10.3389/fevo.2016.00079
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Status Signal Reflects Outcome of Social Interactions, but Not Energetic Stress

Abstract: Social defeat induces stress-responses in a wide array of vertebrates and can generate winner-loser effects. Dynamic condition-dependent signaling systems that reflect preparation for subsequent agonistic interactions, and thereby mediate winner-loser effects, should be more sensitive to competitive history than to non-social sources of stress. Bill color of female American goldfinches (Spinus tristus) is a dynamic condition-dependent ornament that functions as a signal of competitive status and mediates intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…Research in American goldfinches (Spinus tristis) found evidence for the badge-of-status hypothesis: in females, bill coloration was not affected when flying capacity was experimentally impaired. However, it was impacted when social costs were experimentally increased (i.e., artificially creating winners and losers during social interactions leads to respectively increase bill coloration in winners and decrease coloration in loser: Tarvin et al, 2016a). A comparative study found a similar result: carotenoid-based bill coloration seemed to be more correlated with indices of sociality (sociality over the winter, coloniality) than with indices of sexual selection .…”
Section: (I) Cost As a Constraint In The Evolution Of Female Coloration?mentioning
confidence: 97%
“…Research in American goldfinches (Spinus tristis) found evidence for the badge-of-status hypothesis: in females, bill coloration was not affected when flying capacity was experimentally impaired. However, it was impacted when social costs were experimentally increased (i.e., artificially creating winners and losers during social interactions leads to respectively increase bill coloration in winners and decrease coloration in loser: Tarvin et al, 2016a). A comparative study found a similar result: carotenoid-based bill coloration seemed to be more correlated with indices of sociality (sociality over the winter, coloniality) than with indices of sexual selection .…”
Section: (I) Cost As a Constraint In The Evolution Of Female Coloration?mentioning
confidence: 97%
“…By contrast, bill color mediates dominance interactions among female, but not male, American Goldfinches (Murphy et al 2009(Murphy et al , 2014. Bill color not only shapes the outcome of these interactions but responds to it, with color increasing in winners and decreasing in losers (Tarvin et al 2016). Additionally, it appears that social interactions could possibly have such a strong influence on bare-part color that it obscures relationships with condition.…”
Section: Bare Parts In Competitive Interactionsmentioning
confidence: 97%
“…Some degree of bare-part color is often found in both sexes. Despite clear evidence that females display condition dependence in bare parts (Gladbach et al 2010, Kelly et al 2012, Rosenthal et al 2012, Doutrelant et al 2013 and use them for signaling (Nolan et al 2010, Dey et al 2014, Tarvin et al 2016, there has been little study of female bare parts in relation to those of males. Females experience intrasexual competition largely for high-quality mates (Rosvall 2011), and their bare parts can play an important role in competitive interactions (Murphy et al 2009) and male mate choice (Torres and Velando 2005, Cornwallis and Birkhead 2007a.…”
Section: The Importance Of Avian Bare Parts As Signalsmentioning
confidence: 99%
“…Despite clear evidence that females display condition dependence in bare parts (Gladbach et al 2010, Kelly et al 2012, Rosenthal et al 2012, Doutrelant et al 2013 and use them for signaling (Nolan et al 2010, Dey et al 2014, Tarvin et al 2016, there has been little study of female bare parts in relation to those of males. Females experience intrasexual competition largely for high-quality mates (Rosvall 2011), and their bare parts can play an important role in competitive interactions (Murphy et al 2009) and male mate choice (Torres and Velando 2005, Cornwallis and Birkhead 2007a.…”
Section: The Importance Of Avian Bare Parts As Signalsmentioning
confidence: 99%